2021
DOI: 10.3390/cancers13153814
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes for Primary and Radiation-Associated Angiosarcoma of the Breast with Multimodal Treatment: Long-Term Survival Is Achievable

Abstract: Background: The optimal management of primary angiosarcoma (PAS) and radiation-associated angiosarcoma (RAAS) of the breast remains undefined. Available data show persistently poor survival outcomes following treatment with surgery or chemotherapy alone. The objective of this study was to evaluate long-term outcomes in patients treated with multimodality therapy. Methods: Patients diagnosed with stage I–III PAS or RAAS of the breast were identified from our local tumor registry (2010–2020). Patient demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Coincidentally, our results [5] were published 4 days later after the study carried outby Kronenfeld et al [1]. Both analyses obviously represented different RAASB situations in completely different tumor stages.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Coincidentally, our results [5] were published 4 days later after the study carried outby Kronenfeld et al [1]. Both analyses obviously represented different RAASB situations in completely different tumor stages.…”
supporting
confidence: 62%
“…On 2 July 2021, Kronenfeld et al [1] published an excellent analysis of the clinical outcomes of primary angiosarcomas of the breast (PAS) and radiation-associated angiosarcomas of the breast (RAASB) treated with multimodality therapy in the last decade (2010-2020). They concluded, that a multimodal treatment approach that included neoadjuvant chemotherapy (NAC), radiation therapy (RT) in selected patients, surgery (S), and adjuvant chemotherapy (AC) may result in improved outcomes, including prolonged survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given poor overall outcomes and high risk of metastasis in patients with primary angiosarcoma of the breast, multimodal therapy with surgery, systemic chemotherapy, and radiation therapy has been suggested in recent literature. Chemotherapy may reduce the rate of local recurrence and increase rates of complete pathologic response (6,19). A systematic review of literature on angiosarcoma showed a beneficial role of neoadjuvant chemotherapy on downsizing tumors resulting in improved resection margins but showed no clear survival benefit (20).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high incidence of local recurrence, adjuvant radiation therapy may be considered as a possible therapeutic option. Kronenfeld et al published an analysis of clinical outcomes of primary angiosarcomas and radiation-associated angiosarcomas of the breast treated with neoadjuvant chemotherapy, radiation in select patients, surgery, and adjuvant chemotherapy (19). They concluded that this multimodal treatment approach may lead to improved outcomes including prolonged survival (19).…”
Section: Discussionmentioning
confidence: 99%